Hubungan Gaya Kepemimpinan Kepala Ruang Dengan Perilaku Kerja Perawat Pelaksana Rumah Sakit Swasta Di Yogyakarta - Yullya Permina; Vivi Retno Intening (Jurnal Kesehatan, 2025)
Leadership has various ways to influence members in carrying out tasks to achieve predetermined goals. Effective leadership can motivate and encourage nurses to be actively involved in their work, enabling them to complete tasks efficiently and achieve improved work results. Initial research indicates that nurses on duty primarily fulfill their roles because they follow instructions from their leaders. This study aims to identify the relationship between effective leadership styles of the Head of the Ward and the Work Behavior of Nurses in Private Hospitals in Yogyakarta. The method used in this study is quantitative with a cross-sectional study approach. The sampling technique employed is purposive sampling, with a total of 88 nurses serving as respondents. Through the Spearman rank statistical test, a p-value of less than 0.001 with a significance of α=0.05 was obtained, which indicates a relationship between the Leadership Style of the Head of the Ward and the Work Behavior of Nurses in Private Hospitals in Yogyakarta, with a correlation coefficient of 0.752, indicating that the relationship is very strong.